Archie Asbridge with other people at Resolute Bay - (Creator); (Contributor) (2007)
Archie writes: From left, myself then Frank Pierce (USWB tech) the a bearded USWB tech (name forgotten) then a military type, then, a USWB tech whose first name might be DON.